Manajemen Kinerja Anggota Komisi D DPRD Kabupaten Jember dalam Pelaksanaan Fungsi Pengawasan Bidang Pendidikan Dan Kesehatan - Muhammad Nur Aji Aji; Yuniorita Indah Handayani; Dedy Wijaya Kusuma (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
Purpose: This study was motivated by the suboptimal implementation of the legislative oversight function in the education and health sectors, as reflected in low service quality, uneven distribution of resources, and limited program transparency. These conditions indicate the need to strengthen performance management within Commission D of the Regional House of Representatives of Jember Regency. This study aims to analyze performance management, identify efforts to overcome existing obstacles, and formulate an ideal performance management model in the implementation of the oversight function. Research Design and Methodology: The research employed a qualitative approach using a case study strategy. Informants were selected purposively and included the leadership, members of Commission D, and related stakeholders. Data were collected through observation, in-depth interviews, and documentation, and were analyzed using an interactive model. Findings and Discussion: The findings show that the performance management of Commission D is divided into three main stages: planning, implementation, and evaluation. Planning was conducted in an integrated, collective, and adaptive manner according to sectoral needs. The implementation of oversight was responsive, flexible, and collegial in addressing field dynamics. Performance evaluation was carried out dialogically, comprehensively, and adaptively by assessing service aspects, program conformity, and budget absorption. The study also found that obstacles such as resistance from oversight objects, limited data transparency, and constraints related to time, budget, and internal dynamics were addressed through persuasive communication, strengthened formal coordination, and improved internal capacity. Implications: The study implies the importance of strengthening structured performance management systems, improving transparency and inter-institutional collaboration, and enhancing the competence of legislative members to ensure more effective, accountable, and responsive oversight in improving public service quality in the education and health sectors.